Long-term deposit funding and demand for central bank funds: Evidence from targeted longer-term refinancing operations - Adina-Elena Fudulache; Martin R. Goetz (Deutsche Bundesbank, 2023)
We exploit variation in the share of seniors across European banking markets to construct an IV for banks' dependence on long-term deposit funding and find that greater long-term deposit funding reduces demand for long-term central bank funding via targeted longer-term refinancing operations (TLTRO). This effect is stronger when banks face less competition. Long-term central bank funding further motivates banks to reduce their dependence on debt issuance and increase their money markets borrowing. Our findings are consistent with the idea that banks' access to stable funding can crowd out their incentive to apply for (long-term) central bank funding.
Keywords: E50; G20; G28; 330; Monetary policy; bank funding; deposit financing